2001
DOI: 10.1103/physreva.64.043607
|View full text |Cite
|
Sign up to set email alerts
|

Zero-sound density oscillations in Fermi-Bose mixtures

Abstract: Within a mean field plus Random-Phase Approximation formalism, we investigate the collective excitations of a three component Fermi-Bose mixture of K atoms, magnetically trapped and subjected to repulsive s-wave interactions. We analyze both the single-particle excitation and the density oscillation spectra created by external multipolar fields, for varying fermion concentrations. The formalism and the numerical output are consistent with the Generalized Kohn Theorem for the whole multispecies system. The calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…[9] for a mixture with concentric external potentials. This model has been called the double-parabola model by Vichi et al [9], and it has also been used by Capuzzi and Hernández [19]. However, in these works the possibility of a displacement between the minima of the potentials has not been considered.…”
Section: ͑12͒mentioning
confidence: 99%
“…[9] for a mixture with concentric external potentials. This model has been called the double-parabola model by Vichi et al [9], and it has also been used by Capuzzi and Hernández [19]. However, in these works the possibility of a displacement between the minima of the potentials has not been considered.…”
Section: ͑12͒mentioning
confidence: 99%
“…Substituting these values into (25) and (26), we obtain d 2 ≈ log(4/3)/2 ≈ 0.14. Because inside the boson region in addition, V 2 → 0 when Finally, in h > 1, the fermion density distribution has the surface-peaked peak, and a large part of fermions populate outside the boson region.…”
Section: E Collective Oscillation Modes In Largely Oblate Deformed Tmentioning
confidence: 99%
“…One may then consider a new ground state, which is a superposition of a bosonic and fermionic density fluctuation, in analogy to the dressed states of quantum optics [32]. In the appendix it is shown that such a superposition can result in a state with an energy lower than the state used in this section and in other studies of BoseFermi mixtures [14,15,16,17,18,19,20,23], which do not contain any quantum correlations between the densities of the two gases. This indicates that a dynamical instability signified by Im[ℓ k (ω)] = 0 leads to a lower energy ground state of the Bose-Fermi mixture.…”
Section: Mixture Of Bec and Normal Fermi Gasmentioning
confidence: 99%
“…There have been a number of recent studies of both the ground state properties [14,15,16,17] and the collective modes for the density fluctuations of the coupled gases [18,19,20,21]. These studies have all treated the ground state of the fermions as being that of a normal degenerate Fermi gas.…”
Section: Introductionmentioning
confidence: 99%